Assessing the Impact of Local Wisdom on Indonesian Language Learning in Primary Schools - Setyowati, Elis; Hendratno, Hendratno; Sukartiningsih, Wahyu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This article aims to examine the impact of local wisdom on the effectiveness of Indonesian language learning and how the integration of local values can improve students' motivation and understanding. The research method used is SLR research (Systematic Literature Review). The stages of this method are Planningode, Data Collection, Analysis Stage, and Synthesis. Through a literature review of ten relevant journals, this research identifies various positive aspects, such as increased student engagement, character development, and enrichment of the learning context. However, it also found challenges in implementing local wisdom, including a lack of resources and training for teachers. The results of this study show that the application of local wisdom in Indonesian language learning not only enriches students' learning experience but also strengthens their love for their culture and language. Recommendations for educators and education policymakers are proposed to integrate local wisdom more systematically in the curriculum.